Avaliação da qualidade da distribuição de calcário por distribuidores centrífugo e gravimétrico - Magni, Rafael Schmidt (2013)
Currently Brazil grows increasingly in rates of food production, which enables national and international expancion , year after year , growth rates have grown rapidly , and agricultural expansion becomes necessary. Territorial expansion has necessitated the search for adversal regions for the development of the modalities, and this has brought some concern to producers ,since a large part of the land to be exploited is massive and present acidity with low levels of Ca and Mn . To resolve this problem ,and realized the process of liming , which helps in soil remediation . The study a lims to identify the performance of a centrifugal distributorhaul Hercules 10000, through the application of liming on land not in the city of Impatiens in Rio Grande do Sul, th estudy examined the implementation of a type of limes to need just dolomite in a range of 300 m long x 12 m wide , through a double disccentrifuge equipment , and 6 years to the distributor by gravityand the same held two passes , return to complete the 12 meter swith 4 replicates for each machine . To analyze the segregation of the particles ,collecting trays with checkered grid of 0.50 x 0.50 m willing very 1 meter in length with in the range of application we reused . The averageof4replicationswas no difference between Tray 1 ( 1 m from equipment ) and Tray 6 ( transpassive 12 m ) of 23.75% on the amount of particles small erth an 0.30 mm ( reagents 100 % 1st year ) , where it tray 1 had 88.1 % of these particles and tray 6 has obtained 64.35 % .